Labour emigration trends in India - Semenikhina, Valeriia; Sejkora, Jiří, 1985-; Kováčiková, Viera; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
India is a country with the largest diaspora population in the world with 18 million Indians living outside of their home country and sending the highest remittances back home according to the United Nations report on migration trends from 2020. Most emigrants seek work in other countries and the aim of this thesis is to take a closer look at the relevant trends and patterns of labour emigration from India in the twenty-first century to get a bigger picture about the largest community of migrant workers in the world.
Vedoucí práce: Jiří Sejkora
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses